PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN LANGSUNG DALAM DEMOKRASI PANCASILA DI INDONESIA - Al Hidayat, Nanang (Universitas Muhammadiyah Ponorogo, 2018)
This writing aim for describe precident and vice precident general election in Indonesia democration research methods that use is normative juridical. Research result show there is incompatibility between the precident and vice precident regulation election general system, regulation in article 6 UUD NRI 1945 as weel in article 2 law number 42/2008 about Precident and Vice Precident Election with democration that apply in Indonesia, can seen if. Next in article 6 A paragraph 1 UUD NRI 1945 determine that precident and vice precident selected in one candidate pair with direct by poeple’s, conditions direct selected by the poeple’s if reviewed on philosopical contradictory with number 4 Pancasila essence. Historically Indonesia is an eastern country that has a high spirit of mutual cooperation. This means that the soul of mutual-mutuality and togetherness must be embedded in every Indonesian nation that is manifested in the form of indirect democracy. On sociological remember large Indonesia region And the enormous population and geographical conditions that exist, will certainly be more effective and efficient if the presidential election and vice president by the people's representative agencies because it will be more simple and easy to do and does not take a long time and high costs.